AMICO: optimized detection of galaxy clusters in photometric surveys. Issue 4 (17th October 2017) - Bellagamba, Fabio; Roncarelli, Mauro; Maturi, Matteo; Moscardini, Lauro
Abstract: We present Adaptive Matched Identifier of Clustered Objects (AMICO), a new algorithm for the detection of galaxy clusters in photometric surveys. AMICO is based on the Optimal Filtering technique, which allows to maximize the signal-to-noise ratio (S/N) of the clusters. In this work, we focus on the new iterative approach to the extraction of cluster candidates from the map produced by the filter. In particular, we provide a definition of membership probability for the galaxies close to any cluster candidate, which allows us to remove its imprint from the map, allowing the detection of smaller structures. As demonstrated in our tests, this method allows the deblending of close-by and aligned structures in more than 50 per cent of the cases for objects at radial distance equal to 0.5 × R 200 or redshift distance equal to 2 × σ z, being σ z the typical uncertainty of photometric redshifts. Running AMICO on mocks derived from N -body simulations and semi-analytical modelling of the galaxy evolution, we obtain a consistent mass–amplitude relation through the redshift range of 0.3 < z < 1, with a logarithmic slope of ∼0.55 and a logarithmic scatter of ∼0.14. The fraction of false detections is steeply decreasing with S/N and negligible at S/N > 5.